The Extent of Inclusion of Mathematical Knowledge Components in the First-Year Industrial Mathematics Textbook (Journal of the College of Basic Education, 2025)
The current study aimed to identify the extent to which the first-year Industrial Stream Mathematics textbook includes components of mathematical knowledge. To achieve this goal, the researchers employed a descriptive-analytical approach and utilized a content analysis checklist based on four main components of mathematical knowledge, encompassing sixteen related. indicators.The study’s findings revealed that the textbook addresses the components of mathematical knowledge to varying degrees. These components were included in the following order: skills, generalizations, concepts, and problem-solving.In light of these results, the researchers recommend revising and developing the mathematics curriculum for the industrial stream to ensure a more structured progression of mathematical knowledge—particularly emphasizing mathematical concepts, as they are the foundation of this structure.